Quantifying multiple ecosystem services for adaptive management of green infrastructure. Issue 11 (16th November 2018) - Wong, Christina P.; Jiang, Bo; Kinzig, Ann P.; Ouyang, Zhiyun
Abstract: Demands for ecosystem service assessments are growing around the world. However, management applications remain limited in part because we lack measurements linking ecosystem characteristics (ecosystem structure and processes) to final ecosystem services. Policymakers need marginal values, changes in final ecosystem services (direct link to human welfare) relative to additional units of ecosystem characteristics (∆final ecosystem services/∆ecosystem characteristics) to assess tradeoffs. Progress, however, has been slow due to confusion on ecological production functions (EPFs) in ecology. Here, we apply a new interdisciplinary approach to craft EPFs to evaluate four ecosystem services using the Yongding River Green Ecological Corridor as our case study. The Yongding Corridor is Beijing's largest, most expensive green infrastructure project (~ $2.5 billion USD), constructed as a network of seven artificial lakes and wetlands. The Beijing Government wants the Yongding Corridor to improve four ecosystem services: (1) water storage, (2) local climate regulation, (3) water purification, and (4) aesthetics. We first worked with stakeholders to determine final ecosystem service levels and then used the Variable Infiltration Capacity model to estimate key ecosystem processes from the designed lakes and wetlands. We coupled the modeling with ecological field data and social surveys to create EPFs. We evaluated the ecosystem services by calculating shortfalls and then determined synergies and tradeoffs to identify actions for reducing shortfalls. We found the Yongding Corridor is meeting desired levels for aesthetics, but incurred shortfalls on the remaining services. To obtain the desired services, we recommend managers: (1) maintain inflow rates and/or make the lakes deeper to reduce water loss rates; (2) improve water quality—wetlands have high nutrient retention, but nutrient loads must be reduced; and (3) plant shade trees since evaporative cooling from the lakes and wetlands is having no measurable impact on human comfort. Results indicate the absence of ecosystem functions in landscape design led to shortfalls, but solutions require coupling green and built infrastructure to obtain multi‐functionality. Managers found marginal values useful for clarifying connections, which led to adaptive policy changes for improving green infrastructure.